The macroeconomic determinants of the adoption of IFRS for SMEs - Bonito, A.; Pais, C. (Revista de Contabilidad - Spanish Accounting Review, 2018)
The objective of this study is to analyze the macroeconomic factors that influence the decision of the countries in the adoption of International Financial Reporting Standards (IFRS) for small and medium-sized entities (SMEs). Based on a sample of 84 countries, it is found evidence that countries without a national set of financial accounting standards for SMEs, experience in the application of IFRS and a common law legal system are more likely to adopt IFRS for SMEs. However, the level of education, the level of foreign aid received by a country, the quality of accounting standards and the relationship between accounting and taxation have no impact in the national adoption decision of IFRS for SMEs. Additionally, it is found that European Union (EU) member countries are less likely to adopt the standard. Knowledge of macroeconomic factors affecting the national adoption decision of IFRS for SMEs is useful for a several numbers of entities that define the international accounting harmonization, as the IASB, regulators and international accounting firms, since this information can help them in promoting worldwide adoption of the standard.